Model of Jigsaw Type Cooperative Learning Influence on Mathematical Reasoning Ability - Ibrahim Akhid ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2020)
Abstract The purpose of this study was to determine: students' responses to the jigsaw type cooperative learning model, the ability of mathematical reasoning with the application of a jigsaw type cooperative learning model, the effect of applying the jigsaw type cooperative learning model to mathematical reasoning abilities. Data collection techniques used were questionnaires and tests. The population is all students of MTs Al-Munawwir. The research sample is class VII with the sampling technique using cluster random sampling. The results of this study are obtained a positive response to the use of the jigsaw cooperative learning model of 77.10% and the average value of mathematical reasoning ability is 76.54. After testing the hypothesis, it is obtained that tcount(2,375) > ttable(1,708), then Ho is rejected and Ha is accepted, meaning that there is an effect of the application of the Jigsaw type cooperative learning model to the ability of mathematical reasoning. Regression equation Ŷ=33.127+0.447 X.